Stepwise Covariance-Free Common Principal Components (CF-CPC) With an Application to Neuroscience - Riaz, Usama; Razzaq, Fuleah A.; Hu, Shiang; Valdés-Sosa, Pedro A. (Frontiers in Neuroscience, 2021)
Finding the common principal component (CPC) for ultra-high dimensional data is a multivariate technique used to discover the latent structure of covariance matrices of shared variables measured in two or more k conditions. Common eigenvectors are assumed for the covariance matrix of all conditions, only the eigenvalues being specific to each condition. Stepwise CPC computes a limited number of these CPCs, as the name indicates, sequentially and is, therefore, less time-consuming. This method becomes unfeasible when the number of variables p is ultra-high since storing k covariance matrices requires O(kn^2) memory. Many dimensionality reduction algorithms have been improved to avoid explicit covariance calculation and storage (covariance-free). Here we propose a covariance-free stepwise CPC, which only requires O(kn) memory, where n is the total number of examples. Thus for n<